Effect of Low-Cost Technology on Biology Students’ Academic Performance in Ilorin, Nigeria - Ebenezer Omolafe Babalola; Charles Olabode Olumorin; Barakat Barakat; Eyiyemi Veronica Omolafe (Journal of Digital Learning and Education, 2022)
This study examined the effect of Low-cost Technology on Secondary School students’ academic performance in Biology. Quasi-experimental research of post-test non-randomized control group design was adopted for this study. This design was adopted to compare the performance of students who were taught the concept of biology with low-cost technology and those taught without the low-cost technology. Two intact classes from two secondary schools were randomly sampled.  The instruments used were Lesson Note (LN), Biology Performance Test (BPT) for data gathering, and Low-Cost Technology (3D Model of Plant and Animal Cells). BPT was subjected to pilot testing and a reliability coefficient of 0.87 was obtained using the Kuder Richardson KR-20. Two research questions and two research hypotheses were formulated for the study. Findings show that the 3D Model of Plant and Animal Cell significantly influences the understanding of the topic “Plant and Animal Cells” among students irrespective of their gender and institutional ownership. Secondary school teachers should make use of those low-cost technological resources available in their environment for the production of instructional materials.